FINRA arbitration and enforcement : a legal and practice guide - Cohen, Mark S.; Gresser, Lawrence; Stewart, Charles E. (Charles Evan), 1952-; Tabak, Daniel H.; Silikovitz, Harvey B.; Bloomberg BNA ([Arlington, Va.] : Bloomberg BNA, 2014)
"... examines proceedings involving the Financial Industry Regulatory Authority (FINRA) in its dual capacities as a forum for dispute resolution and as a securities industry regulator. The portfolio begins with a discussion of the FINRA arbitration process for the resolution of disputes between member firms, associated persons, and customers. Included is a review of the applicable arbitration codes, and an examination of prehearing matters, motion practice, hearings, and awards. This portion of the portfolio concludes with a discussion of the procedures for confirming, modifying and vacating arbitration awards. The portfolio then examines enforcement actions brought by FINRA against member firms and their associated persons. This chapter reviews FINRA investigations, the disciplinary proceeding process, and the procedures for appeals from or the review of decisions rendered in a FINRA disciplinary proceeding."
Detailed analysis. FINRA arbitration proceedings -- Arbitrator selection and pre-hearing matters -- Motion practice -- Hearings and awards -- Judicial motions to confirm, vacate or modify the award, FINRA investigations and enforcement actions.
Includes bibliographical references.
Description based on contents viewed on May 25, 2015; title from portfolio description screen.
Keywords: Financial Industry Regulatory Authority; Securities -- United States; Arbitration and award -- United States; Financial services industry -- Law and legislation -- United States